DOI: 10.17077/etd.9mkjnsvh
|View full text |Cite
|
Sign up to set email alerts
|

Prediction in aging language processing

Abstract: for participating as members of my thesis committee and for their support and influential roles in my graduate education overall. I would like to thank Effie Kapnoula for her help and advice throughout my studies and for all the scientific (and other) talks we had the last ten years. I would also like to thank my fellow PhD students for their support, encouragement, and feedback Shaorong Yan, Larissa Jordan, and Tanja Roembke. I wish to thank my parents, Dimitris and Theodora, whose unconditional love and supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 171 publications
(268 reference statements)
0
1
0
Order By: Relevance
“…Past studies on the demographics of MTurk workers, for instance, suggest that they cover a broad range of education levels and socio-economic statuses (Ross et al, 2010). As predictive processing during language comprehension has been suggested to be affected by age (though the literature is unclear on the effect of age, with some suggesting a decreased use of prediction (Federmeier et al, 2010;Wlotko et al, 2012), while others have found either no clear effect (Dave et al, 2018), or an effect in the opposite direction (Cheimariou, 2016)), working memory (Huettig and Janse, 2016), as well as language and literacy skills (Kukona et al, 2016;Falkauskas and Kuperman, 2015), the increased variability in our English participants' backgrounds may mean that, across our sample, not all participants may engage in predictive language processing as reliably as the university students participating in the German experiment. For that reason, we assume that a contextual cue effect could still be present in English, and detectable with a larger sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies on the demographics of MTurk workers, for instance, suggest that they cover a broad range of education levels and socio-economic statuses (Ross et al, 2010). As predictive processing during language comprehension has been suggested to be affected by age (though the literature is unclear on the effect of age, with some suggesting a decreased use of prediction (Federmeier et al, 2010;Wlotko et al, 2012), while others have found either no clear effect (Dave et al, 2018), or an effect in the opposite direction (Cheimariou, 2016)), working memory (Huettig and Janse, 2016), as well as language and literacy skills (Kukona et al, 2016;Falkauskas and Kuperman, 2015), the increased variability in our English participants' backgrounds may mean that, across our sample, not all participants may engage in predictive language processing as reliably as the university students participating in the German experiment. For that reason, we assume that a contextual cue effect could still be present in English, and detectable with a larger sample size.…”
Section: Discussionmentioning
confidence: 99%